Glutamate dysregulation and glutamatergic therapeutics for PTSD: Evidence from human studies. (10th May 2017) - Averill, Lynnette A.; Purohit, Prerana; Averill, Christopher L.; Boesl, Markus A.; Krystal, John H.; Abdallah, Chadi G.
Abstract: Posttraumatic stress disorder (PTSD) is a chronic and debilitating psychiatric disorder afflicting millions of individuals across the world. While the availability of robust pharmacologic interventions is quite lacking, our understanding of the putative neurobiological underpinnings of PTSD has significantly increased over the past two decades. Accumulating evidence demonstrates aberrant glutamatergic function in mood, anxiety, and trauma-related disorders and dysfunction in glutamate neurotransmission is increasingly considered a cardinal feature of stress-related psychiatric disorders including PTSD. As part of a PTSD Special Issue, this mini-review provides a concise discussion of (1) evidence of glutamatergic abnormalities in PTSD, with emphasis on human subjects data; (2) glutamate-modulating agents as potential alternative pharmacologic treatments for PTSD; and (3) selected gaps in the literature and related future directions.